ANALISIS PERAN PASAR MODAL SYARIAH DALAM MENDORONG PERTUMBUHAN INVESTASI DAN PEREKONOMIAN INDONESIA - Salwa Balqis; Tyara Amanda; Ahmad Wahyudi Zein (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This research seeks to examine, in a comprehensive manner, how the Islamic capital market contributes to investment growth and overall economic performance in Indonesia. Over the last ten years, this market segment has expanded considerably, as seen from rising Islamic stock market capitalization, a growing number of issuers within sharia indices, and an increasing volume of both corporate and government sukuk transactions. A descriptive quantitative approach is applied, drawing on secondary data sourced from the Financial Services Authority (OJK), the Indonesia Stock Exchange (IDX), and the Central Statistics Agency (BPS) covering 2019 to 2024. The results indicate that the Islamic capital market underwent considerable expansion throughout the study period, evident in the rising value of Islamic stock capitalization, sukuk issuance, and the number of market participants. These developments point to a positive link between the expansion of the Islamic capital market, investment activity, and national economic growth. In addition, the growing availability of sharia investment products via digital platforms has broadened participation among retail investors. The study concludes that a stronger Islamic capital market ecosystem, backed by responsive OJK regulation and collaboration between government bodies and sharia financial institutions, can function as a key driver of sustainable economic growth in Indonesia.